Complement C1s deficiency in a male Caucasian patient with systemic lupus erythematosus: a case report - Kleer, Jessica S.; Skattum, Lillemor; Dubler, Denise; Fischer, Ingeborg; Zgraggen, Armin; Mundwiler, Esther; Kim, Min Jeong; Trendelenburg, Marten (Frontiers in Immunology, 2024)
Deficiencies of the early complement components of the classical pathway (CP) are welldocumented in association with Systemic Lupus Erythematosus (SLE) or SLE-like syndromes and severe pyogenic infections. Among these, complete C1s deficiency has been reported in nine cases so far. Here we describe a 34-year-old, male patient who presented with severe, recurrent infections since childhood, including meningitides with pneumococci and meningococci, erysipelas, subcutaneous abscess, and recurrent infections of the upper airways. The patient also exhibited adult-onset SLE, meeting 7/11 ACR criteria and 34 of the 2019 EULAR/ACR classification criteria, along with class IV-G (A) proliferative lupus nephritis (LN). A screening of the complement cascade showed immeasurably low CH50, while the alternative pathway (AP) function was normal. Subsequent determination of complement components revealed undetectable C1s with low levels of C1r and C1q, normal C3 and slightly elevated C4 and C2 concentrations. The patient had no anti-C1q antibodies. Renal biopsy showed class IV-G (A) LN with complement C1q positivity along the glomerular basement membranes (GBM) and weak deposition of IgG, IgM and complement C3 and C4 in the mesangium and GBM. In an ELISA based functional assay determining C4d deposition, the patient's absent complement activity was fully restored by adding C1s. The genome of the patient was analyzed by whole genome sequencing showing two truncating variants in the C1S gene. One mutation was located at nucleotide 514 in exon 5, caused by a nucleotide substitution from G to T, resulting in a nonsense mutation from Gly172 (p.Gly172*). The other mutation was located at nucleotide 750 in exon 7, where C was replaced by a G, resulting in a nonsense mutation from Tyr250 (p.Tyr250*). Both mutations create a premature stop codon and have not previously been reported in the literature. These genetic findings, combined with the absence of C1s in the circulation, strongly suggest a compound heterozygote C1s deficiency in our patient, without additional defect within the complement cascade. As in a previous C1s deficiency case, the patient responded well to rituximab. The present case highlights unanswered questions regarding the CP's role in SLE etiopathogenesis.